The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1021/jf010875c
|View full text |Cite
|
Sign up to set email alerts
|

Black Tea Polyphenols, Theaflavins, Prevent Cellular DNA Damage by Inhibiting Oxidative Stress and Suppressing Cytochrome P450 1A1 in Cell Cultures

Abstract: Tea polyphenols have been demonstrated as chemopreventive agents in a number of experimental models. However, less is known about the mechanism of chemoprevention by black tea compared with that of green tea. Some beneficial properties of theaflavins, the black tea polyphenols, were investigated in the present study. Theaflavins showed inhibitory effects on H(2)O(2)- and tert-butyl hydroperoxide (tBuOOH)-induced cytotoxicity (evaluated by tetrazolium bromide reduction), cellular oxidative stress (detected by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 32 publications
(34 reference statements)
1
55
0
Order By: Relevance
“…Notable among the literature on antioxidants are studies on various teas, especially green tea (51,52). For example, polyphenols in green tea include catechins (‰avan-3-ols) (53,54), while in black tea, thea‰avin formation may be important (54,55). Polyphenols from green and black tea are eŠective antioxidants in model test systems, while tea polyphenols may also chelate pro-oxidant metals (56).…”
Section: Examples Of Anti-mutagen Protection Against Dišerent Classesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notable among the literature on antioxidants are studies on various teas, especially green tea (51,52). For example, polyphenols in green tea include catechins (‰avan-3-ols) (53,54), while in black tea, thea‰avin formation may be important (54,55). Polyphenols from green and black tea are eŠective antioxidants in model test systems, while tea polyphenols may also chelate pro-oxidant metals (56).…”
Section: Examples Of Anti-mutagen Protection Against Dišerent Classesmentioning
confidence: 99%
“…Various types of anti-mutagen appear to act through inhibiting induction of these enzymes, or otherwise interfering with the activation process. For example, black tea polyphenol (thea‰avin) has been shown to be able to reduce the induction of CYP1A1, at least in a human cultured cell line, and this has been suggested as one mechanism by which this class of chemicals can reduce DNA damage, and possibly also reduce cancer risk (55). The activation of speciˆc groups of mutagens resides with other speciˆc classes of enzymes.…”
Section: Examples Of Mechanisms Of Anti-mutagen Protection Against DImentioning
confidence: 99%
“…15 Studies also demonstrated the anti-cancerous activity and suppression of oral squamous cell carcinoma by Curcuma longa 16 Mentha spicata, 17 Withania somnifera, 18 Nigella sativa 19 and Azadirachta indica. 20 Feng, et al 21 reported that Camellia sinensis protects buccal cells from DNA damage caused by reactive oxygen species. Flower sap of Echinacea sp.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products are important ingredients for medicines, in recent years a variety of natural products have been found to inhibit ONOO¯ damage, a large number of studies have shown that flavonoids compounds have strong antioxidant activity [9][10][11][12], and also these compounds have obvious pharmacological effects on cardiovascular disease treatment and anti-tumor [13]. Studies have shown that the antioxidant effect of flavonoids is closely related to the phenol hydroxyl group in the adjacent position.…”
Section: Introductionmentioning
confidence: 99%